Respuesta :

[tex]\bf 3(x-1)^2+2x-7\implies \stackrel{\stackrel{x=3}{\cfrac{}{}}}{3[(3)-1]^2+2(3)-7}\implies 3[2]^2+6-7 \\\\\\ 3[4]+(-1)\implies 12-1\implies 11[/tex]

Nexeby
(hope that helps )

ANSWER: 35

STEP BY STEP:

First rewrite the equation
(sry I cannot do exponents so I put the whole #) ⇩

3(x-1)2 + 2x -7

Then substitute x for what it is, in this case 3.

3(3-1)2 + 2x -7

Distribute

(9-3)2 + 2(3) - 7

Solve what is inside the parentheses

6 2 + 2(3) - 7

Solve exponents

36 + 2(3) - 7

Solve multiplication

36 + 6 - 7

Add

42 - 7

Subtract for final answer

35
ACCESS MORE